Breech preterm infants are at risk of developmental dysplasia of the hip. Issue 8 (12th June 2013) - Quan, Teddy; Kent, Alison L; Carlisle, Hazel
<x xml:space="preserve">Abstract</x> Aim There is uncertainty about the risk of developmental dysplasia of the hip (DDH) in breech preterm infants and therefore uncertainty about the benefits of using ultrasound screening in this population. The aim of this study was to determine if preterm infants born in the breech position are at risk of DDH. Methods A retrospective audit of preterm and term infants born in the breech position was performed to determine the incidence of DDH. Group 1 included breech preterm infants (<37 weeks gestational age) born between 2004 and 2008. Group 2 included breech term infants (≥37 weeks gestational age) born between 2005 and 2007. Infants were screened with clinical examination and ultrasound of the hip and were classified into two outcome groups: positive or negative for DDH. Results Three out of 129 (2.3%) preterm infants screened had DDH. For term infants, 3 out of 163 (1.8%) infants screened had DDH. The odds ratio for DDH in breech preterm infants compared with breech term infants was 1.27 (95% confidence interval 0.25 to 6.40). Conclusion Preterm infants born in the breech position appear to have a similar incidence of DDH to term infants and thus require similar screening guidelines.